Organic Agriculture: Giving Low-Tech a Chance? An overview of the patent landscape (2019)
This research overview the patent landscape of the inputs approved for certified organic agriculture. For this, it explains the tensions in regards to private voluntary standards addressed in certain trade-related forums. A succinct characterization of the economic impact of plant diseases outbreaks in the Dominican Republic -an organic produce exporting countries- follows. It then briefly compares the “public” norms controlling the production and labeling of organic agriculture, with their “private” counterparts. Subsequently, the result of the patent searchers, which were performed taking into account the private voluntary certifiers’ list of validated inputs, is reported. When the data is analyzed quantitatively, the finding suggests that there is no high intellectual property costs required to comply with the examined private voluntary standards. However, a small number of validated fungicides –which are also widely used by organic farmers in the Dominican Republic- may have significant intellectual property access barriers.